AstraZeneca ChAdOx1-S COVID-19 vaccine can be safely administered in patients with EDTA allergy - Syed B. Ali; Griffith Perkins; Dongjae Ryoo; Maverick Lee; Matthew Tunbridge; Chino Yuson; William Smith; Pravin Hissaria; Thanh-Thao Le (Allergy, Asthma & Clinical Immunology, 2022)
Abstract Background Immediate hypersensitivity reactions to COVID-19 vaccines have been postulated to be linked to their excipients, such as polyethylene glycol (PEG) in Pfizer Comirnaty, or polysorbate 80 and ethylenediaminetetracetic acid (EDTA) in AstraZeneca ChAdOx1-S [recombinant] (Vaxzevria). These excipients are found in a range of other products, including injectable and oral medications as well as intravenous radiocontrast media (RCM) and various cosmetic products. Patients with proven excipient allergy may be advised to avoid a COVID-19 vaccine containing that excipient and/or potentially cross-reactive excipients. This may result in individual patients not receiving vaccines, especially if an alternate option is not available, and on a broader level contribute to vaccine hesitancy. We present two cases of previously confirmed EDTA anaphylaxis with positive intradermal testing, who had negative Vaxzevria vaccine in-vivo testing and subsequently tolerated the vaccine. Case 1 A patient with history of anaphylaxis to RCM and local anaesthetics (LA) had positive intradermal test (IDT) to EDTA nine years earlier. Skin testing to Vaxzeria vaccine (up to 1:10 IDT), Comirnaty vaccine (up to 1:10 IDT) and EDTA 0.3 mg/mL IDT were negative. However, following EDTA 3 mg/ml IDT, he developed immediate generalised urticaria without anaphylaxis. Basophil activation testing was negative to disodium EDTA, Vaxzevria and Cominarty vaccines. Given the negative in-vitro and in-vivo testing to Vaxzevria vaccine, he proceeded to Vaxzevria immunisation and tolerated both doses. Case 2 A patient with history of anaphylaxis to RCM had positive skin testing to EDTA and RCM containing EDTA six years earlier. Following referral to COVID19 vaccine clinic, Vaxzevria vaccine (1:10 IDT) and Cominarty vaccine (1:10 IDT) were negative whilst EDTA was positive at 0.3 mg/mL IDT. He subsequently tolerated both Vaxzevria vaccinations. Conclusion Excipient allergy does not necessarily preclude a patient from receiving a vaccine containing that excipient. Allergy testing can help identify excipient-allergic patients who may still tolerate vaccination, which is important in situations where COVID-19 vaccination options are limited.